The Burden of Klebsiella Infections in Neonates: Incidence, Risk Factors, and Outcomes from Zawia Medical Center - Mufeeda Mansour (Khalij-Libya Journal of Dental and Medical Research, 2025)
Klebsiella species are a major cause of late-onset sepsis and death in newborn intensive care units (NICUs), especially in resource-limited settings. The purpose of this study was to assess the prevalence, risk factors, and clinical outcomes of Klebsiella infections in a tertiary NICU in Libya. A retrospective cohort analysis was carried out, evaluating data of all neonatal patients admitted to the Neonatal/Pediatric ICU at Zawia Medical Center between January and December 2023. A positive culture verified the diagnosis from a sterile location. Data on demographics, clinical risk factors, and results were gathered and evaluated using acceptable statistical techniques. The incidence of Klebsiella infection was 15.4% (19/123). Mechanical ventilation was a significant risk factor, with 74% of infected neonates exposed compared to 24% in the uninfected group (OR: 8.85, 95% CI: 2.9–27.0, p<0.001). Crucially, the administration of blood products was strongly associated with infection: platelets (OR: 8.1, 95% CI: 2.8–23.7, p<0.001), fresh frozen plasma (OR: 5.6, 95% CI: 1.9–16.6, p<0.001), and red blood cells (OR: 4.0, 95% CI: 1.4–11.3, p=0.005). Preterm neonates were also at significantly higher risk (63% vs. 36.5%, p=0.003). All-cause in-hospital mortality was drastically higher in infected neonates (58% vs. 18%, p=0.001), with an attributable mortality of 42%. Kaplan-Meier analysis confirmed a significantly reduced median survival time in the infected group (7 vs. 22 days, log-rank p<0.02). Klebsiella infections are a common and fatal hazard in this context, and mechanical ventilation is an important modifiable risk factor. These findings underline the critical need for strict infection prevention strategies, particularly in ventilator care, as well as improved antibiotic stewardship to improve survival outcomes.